OLAHRAGA NON-PROFIT:LITERATURE REVIEW - Aini, Khurotul; Purwanto, Didik; Rahman, Andi (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2024)
Non-profit sports organizations were developed with the aim of developing athletes into elite athletes who are currently still very dependent on people and voluntary institutions. The development of non-profit sports organizations in Indonesia has the opportunity to develop, because the non-profit sports organizations that are developing are still in the European region. This article aims to provide a general overview of the factors supporting the success of developing non-profit sports organizations in Indonesia. This research uses library observations through library analysis on mendeley.com with the keywords non-profit sports innovation management with steps 1) owning and searching a database, 2) data retrieval and 3) data analysis. Based on the Mendeley database for the last 10 years from 2013 to 2023, 51 relevant articles were found, and up to 8 articles met the eligibility criteria. The limitation of this research is that it can only use the Mendeley database which comes from books, papers, articles, conferences. The findings of this literature study conclude that managerial human resource capabilities in organizations and openness to technological innovation are needed to develop non-profit sports organizations. Some innovations that can be developed are innovations in services from the physical and non-physical fields. This research contributes to the scientific study of the development of non-profit sports organizations in Indonesia as a new force in the development of national sports innovation, which of course still requires more in-depth study in accordance with current needs